Response of a southern rock lobster (Jasus edwardsii) population to three years of Marine Protected Area implementation within South Australia. (21st February 2021) - McLeay, Lachlan; Linnane, Adrian; McGarvey, Richard; Bryars, Simon; Hawthorne, Peter
Abstract: The Western Kangaroo Island Marine Park (WKIMP) was declared as part of South Australia's representative system of Marine Protected Areas in 2009. Sanctuary Zone 3 (SZ-3) of the WKIMP is a no-take area protected from fishing since 1 October 2014 and is located within the Northern Zone Rock Lobster Fishery (NZRLF). In February 2017, a dedicated survey was undertaken to estimate the relative abundance (catch per unit effort (CPUE), kg/potlift) and size of southern rock lobster ( Jasus edwardsii ) inside and outside SZ-3. Survey results were then compared with historical estimates of abundance and size obtained from commercial fishery-dependent data. Survey estimates of relative abundance of legal-size lobsters were 4.4 times greater inside SZ-3 compared with outside in 2017. Since 2014, when fishing was last permitted inside SZ-3, the relative abundance of lobsters increased by 75%. The mean size of legal-size female and male lobsters also increased by 4.1% and 12.5%, respectively. The population responses recorded are consistent with the results recorded for southern rock lobster stocks in marine parks in other jurisdictions.